Immune links in comorbid depression and psoriasis: A narrative mini-review and perspective - Georgia Lada (Brain, Behavior, & Immunity - Health)
Evidence suggests a bidirectional association between psoriasis and depression, which is considered to reflect complex neuroimmunological and psychosocial interactions. Despite an early interest in the brain-skin axis and the role of stress in psoriasis immunopathogenesis, there is ongoing limited preclinical and clinical research into the inflammatory links between depression and psoriasis. Existing findings for serum inflammatory markers of depression in psoriasis are inconsistent and do not fully align with those in the general population, while brain imaging evidence is scarce and has not confirmed direct brain involvement in the systemic inflammation of psoriasis. The present paper reviews the available literature on the immune interplay of psoriasis with depression, highlights the significance of further work in the field and proposes avenues for future research.